2012
DOI: 10.1111/j.1463-1318.2012.03016.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumours of the retrorectal space: management and outcome of a heterogeneous group of diseases

Abstract: Given their complexity, these tumours should be addressed by experts and all treatment options must be contemplated. They continue to present a challenge, above all in malignant tumours where the tumour cannot be controlled at a locoregional level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 24 publications
0
43
0
Order By: Relevance
“…4 in contrast, although solid tumors can be both benign and malignant, many are malignant with a wide range of pathologic subtypes, which complicates their management. [3][4][5][6][7][8] an accurate preoperative diagnosis of solid or heterogeneous tumors in the presacral space is crucial, because the clinical management of benign and malignant lesions differs considerably. surgically, a wide-margin, en-bloc oncologic resection is indicated for most malignant lesions, but a close-margin approach should be attempted for benign lesions to spare function and avoid morbidity.…”
mentioning
confidence: 99%
“…4 in contrast, although solid tumors can be both benign and malignant, many are malignant with a wide range of pathologic subtypes, which complicates their management. [3][4][5][6][7][8] an accurate preoperative diagnosis of solid or heterogeneous tumors in the presacral space is crucial, because the clinical management of benign and malignant lesions differs considerably. surgically, a wide-margin, en-bloc oncologic resection is indicated for most malignant lesions, but a close-margin approach should be attempted for benign lesions to spare function and avoid morbidity.…”
mentioning
confidence: 99%
“…Despite the fact that the majority of tailgut cysts are benign, the current literature shows an increasing risk of malignant transformation [7,13] when the most common histopathologic diagnoses are adenocarcinoma or carcinoid [13]. Interestingly, malignancy is more common in men due to delay in diagnosis; this is because among women the cystic lesions are frequently detected during gynecological examinations [9]. …”
Section: Discussionmentioning
confidence: 99%
“…MRI findings usually correlate slightly more with the final histology of the tumor than CT scan results. Of course, primarily patients must undergo a digital rectal examination and colonoscopy (and additionally, for women, a gynecological examination) to exclude more common conditions [3,9]. Final diagnosis, of course, remains histopathologic [13], but most authors agree that a pre-operative biopsy of the tumor is not indicated because it can be uninformative and the risk of bleeding, infection and dissemination of malignant cells into the peritoneal cavity or seeding of the biopsy tract is high [7,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differential diagnosis is wide and includes a congenital origin in most of cases and neurogenic, osseous or inflammatory origin 2. Congenital cystic lesions are the most common, and they represent up to 40% of retrorectal tumours.…”
Section: Introductionmentioning
confidence: 99%